2015
DOI: 10.30843/nzpp.2015.68.5798
|View full text |Cite
|
Sign up to set email alerts
|

Control of <i>Neonectria ditissima</i> with copper based products in New Zealand

Abstract: New Zealand pipfruit crops require postharvest fungicides for control of European canker, caused by Neonectria ditissima. Fungicide efficacy trials to protect leaf scars from N. ditissima infections were conducted during autumn 2013 and 2014. Disease control of artificially inoculated leaf scars was achieved by single applications of copper oxychloride and copper oxide, but not copper hydroxide, applied at 4.3, 1.1 and 0.6 kg elemental copper/ ha respectively. Control of leaf scar infections by copper oxide (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 12 publications
2
26
0
Order By: Relevance
“…The low expression of leaf-scar infections is disappointing, but this has occurred in other artificially inoculated and naturally infected leaf-scar experiments in the 2015 autumn-winter period (Dryden et al 2016;Walter et al 2017b). Normally, under New Zealand (Tasman) conditions, we would expect 10-20% of leaf scars to develop symptoms within 6 months of artificial inoculation Walter et al 2015;2017b) but in the 2015 autumn-spring period only 4.4 % of leaf scars expressed in the control treatment. This, however, was typical for the 2015 season (Dryden et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The low expression of leaf-scar infections is disappointing, but this has occurred in other artificially inoculated and naturally infected leaf-scar experiments in the 2015 autumn-winter period (Dryden et al 2016;Walter et al 2017b). Normally, under New Zealand (Tasman) conditions, we would expect 10-20% of leaf scars to develop symptoms within 6 months of artificial inoculation Walter et al 2015;2017b) but in the 2015 autumn-spring period only 4.4 % of leaf scars expressed in the control treatment. This, however, was typical for the 2015 season (Dryden et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…age played a role in the susceptibility to infection. Weber (2014) and Walter et al (2015) showed that leaf-scar age <2 days did not affect disease development. The leaf scars inoculated here were 1-day-old.…”
Section: Figurementioning
confidence: 97%
See 2 more Smart Citations
“…Leaf scars were created 10 days after treatment application by removing three (preferably senescent) leaves per shoot. Selected shoots were labelled and leaf scars marked with a paint pen (Walter et al 2015). In each plot, there were up to 30 shoots which were inoculated with a N. ditissima spore suspension (ca 1×10 5 conidia/ml), prepared from naturally occurring canker lesions, as described by Walter et al (2015).…”
Section: Wounds and Inoculationmentioning
confidence: 99%